Acidified bimetallic MOFs constructed Co/N co-doped low dimensional hybrid carbon networks for high-efficiency microwave absorption. (January 2021) - Xu, Xueqing; Ran, Feitian; Fan, Zhimin; Cheng, Zhongjun; Lv, Tong; Shao, Lu; Xie, Zhimin; Liu, Yuyan
Abstract: Metal-organic frameworks (MOFs) derived carbon-based nano/micro-structured composites are booming as a promising class of microwave absorption (MA) material. However, rational design MOFs derived MA materials with interconnected low dimensional hybrid networks are still challenging but significant for boosting the MA performances. Herein, 3D Co/N co-doped carbon networks with hybrid different low dimensional units, including carbon nanosheet framework (H-700), bamboo-like carbon nanotube interpenetrated carbon nanosheet hybrid network (H-800), and interweaved bamboo-like carbon nanotube network attached carbon nanosheet (H-900) have been controllably fabricated through pyrolyzing the acidified bimetallic ZIF-L. Moreover, hybrid network structures are favoring electron transportation, interface polarization, multiple loss, as well as impedance matching. Consequently, the H-800 exhibits a strong absorption ability with minimum reflection loss of −56.2 dB, while the H-900 has a broad absorption bandwidth of 5.2 GHz with thin thickness (1.8 mm) and low weight ratio (10 wt%). This work presents a novel strategy to construct the low dimensional hybrid networks from MOFs for expanding more potential application. Graphical abstract: The 3D Co/N co-doped hybrid carbon networks with different low dimensional units, have been controllably fabricated through pyrolyzing the acidified bimetallic ZIF-L. Moreover, the unique structures of low dimensional hybrid carbon networks endow them lightweight characteristic and excellent MA performances. Image 1 Highlights: The Co/N Co-doped interconnected low dimensional hybrid carbon networks were successfully constructed from the acidified bimetallic MOF. The controlling of pyrolysis temperature effectively adjusted the microstructure of low dimensional hybrid carbon networks. The low dimensional hybrid nanostructures exhibit excellent microwave absorption performances.